The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1136/aim.23.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Laser Acupuncture for Mild to Moderate Depression in a Primary Care Setting – a Randomised Controlled Trial

Abstract: Objective Depression is a major public health problem. There is some evidence supporting the effectiveness of needle acupuncture in its treatment. Laser stimulation, regarded here as a modality of acupuncture, is non-invasive and therefore free of infection risk; and it is acceptable to patients with needle phobia. The technique is relatively easily learned by community-based general practitioners. It is also amenable to sham control and therefore double-blinding in clinical trials. A double-blind randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 24 publications
1
52
0
2
Order By: Relevance
“…11 We demonstrated that stimulation of acupoints LR 8, LR 14, and CV 14 activated and deactivated many brain regions, including those that are known to be involved in the regulation of mood and which are putative targets in any antidepressant treatment. 18 In particular, these regions were the cingulate gyrus, the parahippocampal gyrus, and the striatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We demonstrated that stimulation of acupoints LR 8, LR 14, and CV 14 activated and deactivated many brain regions, including those that are known to be involved in the regulation of mood and which are putative targets in any antidepressant treatment. 18 In particular, these regions were the cingulate gyrus, the parahippocampal gyrus, and the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…4 All except one were needle acupuncture studies, with one double-blind, controlled study that examined laser acupuncture reporting a highly significant positive effect of the treatment. 11 The Cochrane review concluded that there was insufficient evidence for the use of acupuncture in depression. It is noteworthy that none of the studies reviewed was supported by neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
“…The laser parameters are similar to the one used in the clinical study we have based our investigation upon [22]. The acupoints were marked with a skin marking pencil prior to entry into the scanning room.…”
Section: Laser Stimulationmentioning
confidence: 99%
“…In practice, acupoint efficacy is not specific, and one acupoint can be used for several different conditions, just as one medical condition can be managed with several acupoint locations. For instance, the antidepressant effect of laser acupuncture [22] has been attributed to a group of acupoints -CV14, LR14, LR8 and HT7 (see fig.1 for anatomical location), however there are other acupoint combinations that are also applicable for the management of depression. The neurological effects of stimulation of these acupoints CV14, LR14, HT7 and LR8 in combination have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increase in its popularity, there has been a recent diversification of acupuncture research away from the more traditional study of pain 3 into the examination of the role of acupuncture in mental disorders. [4][5][6][7][8][9][10][11][12][13] The first foray into the use of acupuncture in the treatment of depression was the investigatory work on electroacupuncture. 6,7 These earlier studies were followed by clinical studies from 1998 when the use of manual needle acupuncture in depression was revisited.…”
Section: Introductionmentioning
confidence: 99%